2012
DOI: 10.1093/ckj/sfs100
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function, urinalysis abnormalities and correlates in equatorial Africans with sickle cell disease

Abstract: BackgroundLittle is known about the renal profiles of individuals with sickle cell disease (SCD) in equatorial Africa, the global epicenter of SCD. We evaluated the kidney function, urinalysis abnormalities and their correlates in a group of Cameroonians homozygous for SCD.MethodsThis was a cross-sectional study of 4-month duration involving 72 homozygous SCD patients (39 men, 54%), recruited during routine visit or vaso-occlusive crisis at the Yaoundé Central Hospital in Cameroon. Clinical and laboratory data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…Laboratory data included serum and urinary creatinine, and urinary protein. The methods for urine and blood specimen analysis at the Yaoundé Central Hospital’s laboratory have been described in details elsewhere [ 20 ]. Secondary variables were derived from primary variables using validated formulas.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory data included serum and urinary creatinine, and urinary protein. The methods for urine and blood specimen analysis at the Yaoundé Central Hospital’s laboratory have been described in details elsewhere [ 20 ]. Secondary variables were derived from primary variables using validated formulas.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, recent studies underline SCT as a risk factor of chronic kidney disease in Africans Americans [10]. In a Cameroon, Kaze, et al reported high frequency of proteinuria (94%) compare to other African studies [11,12]; other kidney abnormalities were leucocyturia (78%), hematuria (14%) and low estimated glomerular filtration rate (1.5%). However, the exact prevalence of chronic kidney disease in SCA is not known since the persistence of these anomalies at 3 months was not evaluated.…”
Section: Introductionmentioning
confidence: 94%
“…The maximum urinary concentration declines with age in SCA and SCT [39]. Subsequent studies, using urine specific gravity or urine osmolality, demonstrated hyposthenuria in SCA and SCT as well [40][41][42].…”
Section: Enuresis In Sca: the Postulated Etiologymentioning
confidence: 99%